Pattern of road tra!c injuries and disability burden among accident victims (Bangladesh Medical Journal, 2019)
Worldwide road traffic injuries cause more than 1.2 million deaths every year and alarming rise has been observed in road accidents in Bangladesh over the past few years. A cross- sectional study was carried out from January to December 2017 to determine the pattern of road traffic injuries with disability burden among accident victims. 190 respondents were selected from Center for the rehabilitation of the paralyzed (CRP) at Savar and Mirpur in Dhaka by purposive sampling. Data was collected by face to face interview by using semi-structured pre-tested questionnaire. A large number of accident victims in this study were male (79.5%), Muslim (93.2%), married (85.3%) with middle age group (35.8%). Most of the accident victims came from rural area (62.6%) and place of most accident occurred in subway (73.1%). Highest number of accident occurred by motorized two wheels (47.3%). Fracture (48.9%) were most common types of injury among accident victims and affected part were most commonly the extremities (32.9%) and injury category were maximum injury (38.9%). Years of life lived with disability was highest in spinal cord injury (172.36). Among those who were in middle age group, suffered longer than other injury with years of life lived with disability. It found people who were injured from motorized two wheels had suffered longer years lived with disabilities of life than other types of vehicle injury(82.02).The result indicates the pattern of injuries and accident victims who were lived with disability for long time.Bangladesh Med J. 2018 Jan; 47 (1): 28-32